Patriotic upbringing of young citizens as one of key factors at education institutions in Ukraine - Sazanova, L. S.; Сазанова, Л. С. (Current trends in scientific research development:The 2nd International scientific and practical conference (Boston, USA, September 19-21, 2024). - Boston, 2024. - P. 149-157, 2024)
Проаналізовано сучасні засоби і методи національно-патріотичного виховання майбутніх поліцейських на заняттях з іноземної мови. Зазначено, що навчання та виховання курсантів перебуває під постійним наглядом викладача. Завдання національно-патріотичного виховання курсантів йдуть поруч із формуванням іншомовної комунікативної компетенції. Підкреслено, що ефективність патріотичного виховання залежить від спрямованості виховного процесу та методів його організації.

The purpose of the article is to analyze modern means and methods of national and patriotic education of future police officers in foreign language classes. It is stated that cadets’ teaching and upbringing is under constant teacher’s supervision. The tasks of national and patriotic education of the cadets go along with the formation of foreign language communicative competence. It is said that the effectiveness of patriotic education depends on the orientation of the educational process and methods of the organization.

Проанализированы современные средства и методы национально-патриотического воспитания будущих сотрудников полиции на занятиях по иностранному языку. Отмечено, что обучение и воспитание курсантов находится под постоянным контролем преподавателя. Задачи национально-патриотического воспитания курсантов неразрывно связаны с формированием иноязычной коммуникативной компетенции. Подчеркнуто, что эффективность патриотического воспитания зависит от направленности образовательного процесса и методов его организации.
Keywords: національно-патріотичне виховання; патріотизм; методи виховання; засоби виховання; методи навчання; національне виховання; працівники поліції; іноземна мова; national and patriotic education; patriotism; educational methods; means of education; teaching methods; national education; police officers; foreign language; национально-патриотическое воспитание; патриотизм; методы воспитания; средства воспитания; методика обучения; национальное воспитание; сотрудники полиции; иностранный язык